Peran Digital Marketing dalam Meningkatkan Daya Saing UMKM di Era Ekonomi Digital - Fadali Rahman; Adriani Kusuma; Akhmad Maulana Afrizal; Nurul Hidayah Ansori; Rahmadani Rahmadani (Penerbit Jurnal Indonesia, 2025)
The advancement of digital technology has brought significant changes to modern marketing systems, particularly for MSMEs Micro, Small, and Medium Enterprises. In the digital economy era, digital marketing has become a crucial strategy for increasing competitiveness and expanding market reach. Many MSMEs have begun utilizing social media platforms, marketplaces, and websites to effectively promote their products. Through this approach, MSMEs can interact directly with consumers, build brand image, and increase sales without incurring large marketing costs. Digital marketing also provides access to a variety of data and analytics that help businesses understand market behavior and needs, allowing for more precise marketing strategies. However, challenges such as limited digital literacy, a lack of competent human resources, and uneven digital infrastructure remain major obstacles for some MSMEs. Therefore, government support, education, and ongoing training are needed to help MSMEs optimize their digital marketing potential. With the right digital strategy implementation, MSMEs have a significant opportunity to compete more effectively in the increasingly dynamic digital economy.